Manajemen Keuangan Rumah Tangga: Pengenalan Pengelolaan Keuangan Pada Ibu-ibu Peserta Program Keluarga Harapan (PKH) di Kelurahan Kroman, Kecamatan Gresik, Kabupaten Gresik - Khasanah, Uswatun; Vitriya, Rezza; Mufarokhah, Nur (Jurnal ABM Mengabdi, 2023)
Abstract Household financial management is an important thing to do in managing finances. Household Financial Management is the process of managing income, expenses, investments and savings in the family to achieve short-term and long-term financial goals. This introduction to financial management is important for PKH participant mothers so that financial conditions are better so that PKH participant mothers can have financial independence. The participants in this introduction to financial management were PKH participants in Kroman village, Gresik district, Gresik regency. This introductory activity begins with a presentation on the importance of household financial management, followed by a presentation and joint practice on managing household finances in a simple way that PKH participant mothers in the Kroman sub-district can do independently and easily remember. The results of this introduction to finance activity are that PKH participant mothers understand better that income and expenses should be calculated so that they can analyze the current family financial condition. In addition, PKH participants in Kroman district know that debt in the family cannot exceed the financial condition limit. Keywords: , Financial Management, Income, Expenditures, PKH Gresik